Analysis of Branding Strategies in Documentation Services Berdua Pictures to Increase Competitiveness - Bakar, Rafael Habib Abu; Sardanto, Rino (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: Research aims to find out how to increase competitiveness through branding strategies that have been carried out by Berdua Pictures. Design/Method/Approach: This research is a qualitative descriptive research, with data collection techniques through observation, interviews, and documentation to provide in-depth information about the operational situation of the research object. The subjects of the study involved company owners, employees and one consumer as resource persons who provided information related to the context of this study. Research Finding:  the results of this study documentation services of Berdua pictures have used branding strategies according to gelder such as brand positioning, brand identity, brand personality that makes Berdua pictures known (brand awareness) and have an impression (brand image) by utilizing social media such as Instagram and WhatsApp, which can increase the competitiveness of Berdua pictures, by always evaluating performance results and utilizing their advantages. Theoretical contribution/Originality: Implementing the right branding strategy not only creates added value for the product or service, but also allows the company to differentiate itself from competitors, providing an edge in attracting customers and grabbing a larger market share. Practitionel/Policy implication: branding strategy plays a crucial role in increasing brand awareness. The findings show that the implementation of an effective branding strategy is able to form a strong brand image and identity, increasing the level of brand recognition and understanding among consumers. Research limitation:  the research focuses on branding strategies applied by Berdua pictures that can increase competitiveness in the photography industry.